AB0158 Tauroursodeoxycholic acid decreases the expression of erad components and the accumulation of salivary mucins induced by pro-inflammatory cytokines. (15th June 2017) - Albornoz, N; Aguilera, S; Barrera, M-J; Castro, I; Carvajal, P; González, S; Molina, C; Urzúa, U; Jara, D; Leyton, C; González, M-J
Abstract : Background: The salivary glands of Sjögren's syndrome patients show endoplasmic reticulum (ER) stress characterized by intracellular accumulation of secretory products such as MUC1 1, dilated ER cisternae 2 and high levels of pro-inflammatory cytokines. Previous results from our laboratory revealed an increase of the ATF6α pathway of the UPR 3 and activation of ER-associated protein degradation (ERAD) 3 . Increased expression of proteins involved in ERAD (SEL1L and EDEM1) has been reproduced in vitro in human submandibular gland (HSG) cells treated with TNF-α or IFN-γ 2 . Tauroursodeoxycholic acid (TUDCA) is a chemical chaperone utilized for alleviate ER stress by enhancing the folding of proteins 3 . Objectives: The aim of this study was to evaluate if TUDCA decreases EDEM1, SEL1L, and MUC1 expression induced by pro-inflammatory cytokines in salivary gland epithelial cells. Methods: HSG-cells were incubated with 10 ng/mL of IFN-γ or TNF-α for 24h. Alternatively, cells were incubated with cytokines for 6h and then co-incubated with TUDCA (150 and 250 μM) up to 24h. EDEM1, SEL1L and MUC1 protein and mRNA levels were determined by Western-blot and RT-qPCR, respectively. EDEM1 and SEL1L localization was determined by immunofluorescence. Results: HSG cells stimulated with IFN-γ or TNF-α showed a significant increase of EDEM1 and SEL1L protein and mRNA levels. Importantly, TUDCA co-incubation caused a significant decreased expression of both molecules. Treatment with both cytokines induced a cytoplasmic increase of staining intensity of EDEM1 and SEL1L, which was suppressed by TUDCA. HSG cells stimulated with cytokines showed a significant increase of MUC1 protein and mRNA levels, which was also suppressed by TUDCA. Conclusions: Decreased expression of MUC1, SEL1L and EDEM1 in the presence of TUDCA suggests that this chemical chaperone promotes folding of proteins in the ER, by decreasing ERAD activity and ER stress induced by pro-inflammatory cytokines in HSG cells. These results enable us to propose that TUDCA might alleviate the ER stress of salivary glands from Sjögren's syndrome patients. References: Oral Dis. 2015;21(6):730–8. Arthritis Rheum. 2003 Sep;48(9):2573–84. J Autoimmun. 2016;75:68–81. Prion. 2014;8(2). pii: 28938. Acknowledgements: Supported by Fondecyt-Chile [#1160015] (MJG, SA, CM, SG, IC). Disclosure of Interest: None declared